2023
DOI: 10.3389/fcell.2023.1083838
|View full text |Cite
|
Sign up to set email alerts
|

Role of ferroptosis in pregnancy related diseases and its therapeutic potential

Abstract: Ferroptosis is a form of regulated cell death characterized by iron overload, overwhelming lipid peroxidation, and disruption of antioxidant systems. Emerging evidence suggests that ferroptosis is associated with pregnancy related diseases, such as spontaneous abortion, pre-eclampsia, gestational diabetes mellitus, intrahepatic cholestasis of pregnancy, and spontaneous preterm birth. According to these findings, inhibiting ferroptosis might be a potential option to treat pregnancy related diseases. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 168 publications
0
3
0
Order By: Relevance
“…For example, several new cell death related pathways (including necroptosis, pyroptosis, ferroptosis, and cuproptosis) have been found to play important roles in various physiological and pathological processes ( 96 ). Among these pathways, ferroptosis is especially found to be associated with pregnancy related diseases and could be a potential target for therapy ( 97 ). As mentioned above, initial proteomics screening of placenta tissue showed that differentially expressed proteins are highly associated with apoptosis and autophagy based on functional annotation.…”
Section: Suggestions Of New Research Directions For Future Omics Studiesmentioning
confidence: 99%
“…For example, several new cell death related pathways (including necroptosis, pyroptosis, ferroptosis, and cuproptosis) have been found to play important roles in various physiological and pathological processes ( 96 ). Among these pathways, ferroptosis is especially found to be associated with pregnancy related diseases and could be a potential target for therapy ( 97 ). As mentioned above, initial proteomics screening of placenta tissue showed that differentially expressed proteins are highly associated with apoptosis and autophagy based on functional annotation.…”
Section: Suggestions Of New Research Directions For Future Omics Studiesmentioning
confidence: 99%
“…Hypofibrinolytic conditions that increase the risk of fetal growth restriction, apart from emotional responses, include inflammatory conditions as diverse as obesity, 75 autoimmune diseases, 76 silicone breast implants, 77 gut dysbiosis, 78 giardiasis, 79 and ferroptosis, 80 81 a condition associated with iron toxicity characterized by increased levels of TGF-β, as well as hyperhomocysteinemia, 82 hypothyroidism, 83 Cushing's syndrome, 84 and autoantibodies such as antiphospholipid antibodies. 76 85 The PAI-1 4G allele does not seem to contribute to fetal growth restriction, 86 87 supporting the idea that decreased villous branching depends mostly on factors occurring in late pregnancy.…”
Section: Normotensive Fetal Growth Restrictionmentioning
confidence: 99%
“…Recently, ferroptosis, a form of cell death driven by iron-dependent lipid peroxidation, has been associated with the pathogenesis of COPD. [ 1 ] Multiple signaling pathways, such as glutathione peroxidase 4 (GPX4), ferroptosis suppressor protein 1 (FSP1), and tetrahydrobiopterin-dependent pathways, as well as iron metabolism, are involved in regulating ferroptosis [ 2 , 3 ] [Figure 1 A]. Here, we provide a comprehensive overview of recent advances in understanding the role of ferroptosis in COPD, highlighting potential therapeutic strategies targeting ferroptosis for treating the disease.…”
mentioning
confidence: 99%